POSSIBILITIES OF THE USE OF WORKING SELF-CONTAINED BREATHING APPARATUSES FILTRATING CARBON MONOXIDE IN THE PRACTICE OF MINE RESCUE SERVICES - Pavelek, Zdeněk (GeoScience Engineering, 2017)
In the current practice of the Mining Rescue Service of the Czech Republic, since 2005, the insulated overpressure regenerative breathing apparatuses with a closed circuit and supply of medicinal oxygen are used as the backbone working breathing apparatuses. At the end of the year 2010, the compressed-air breathing apparatuses were introduced into the practice of the Mining Rescue Service of the Czech Republic, which, in precisely defined types of mine rescue service interventions and under precisely defined conditions, can replace the aforementioned backbone working insulated overpressure regenerative breathing apparatuses. Recently, mining rescue services in deep coal mines have been more and more often conducted under conditions of an irrespirable mine atmosphere containing high concentrations of carbon monoxide, but at the same time containing sufficient oxygen for the breathing physiology of mine rescuer (for example, interventions dealing with the disposal of machinery under conditions of occurrence of endogenous mining fire of coal). This fact, after a long time, has resumed again the discussion of miners' rescue experts about whether it would be possible to implement the use of breathing apparatuses filtrating carbon monoxide into practice by the Mining Rescue Services of the Czech Republic in order to ensure a sufficient level of safety for mining rescuers even in an unexpected and rapid decline of the oxygen amount in the mine air at the site of the mine rescue service. The benefit of the breathing apparatuses filtrating carbon monoxide is their significantly lower weight, long protection period and also significantly smaller dimensions and design variability of the device. The disadvantages are higher breathing resistances and a higher temperature of the air mass inhaled from the breathing apparatus filtrating carbon monoxide.